Algorithmic game theory : 10th International Symposium, SAGT 2017, L'Aquila, Italy, September 12-14, 2017, Proceedings /: 10th International Symposium, SAGT 2017, L'Aquila, Italy, September 12-14, 2017, Proceedings. (2017) - Unknown
No abstract available